(untitled) (Research, Society and Development, 2022)
The article presents research aimed at identifying the knowledge of teachers in the federal education network regarding the legislation that guides professional and technological education, as well as the way in which this appropriation took place, with a focus on the organization of the pedagogical projects of the courses. The analysis of the training demands of teachers can help in the organization of activities of continuing education in the service of teachers of professional and technological education, in order to meet their specificities and challenges inherent to this type of teaching. With a qualitative and exploratory approach, it involved a case study with the participation of thirteen professors, with data collection taking place through a questionnaire. Among the demands observed, we highlight the need for more knowledge about educational legislation, considered brief and insufficient, to have access to discussions and strategies adopted by federal institutes, and to hold discussions on issues present in the legislation that supports the professional education technology, such as polytechnics, interdisciplinary teaching and integrated. The offer of continuing education courses must be conducted by the federal network itself as an institutional policy, with a constant offer and focused on meeting the needs of the teacher and the institution itself.